Harnessing Mobile Health Technologies to Improve Child Health Outcomes: A Systematic Review of Interventions for Under-5 Year Children in Low- and Middle-Income Countries - Grewal, Manpreet Kaur; Rai, Kanika (National Journal of Community Medicine, 2025)
Introduction: The global health policy's main goal is to reduce the under-five mortality rate (U5MR), especially in low- and middle-income countries (LMICs), where children still die of various ailments. Mobile-Based Health (mHealth) methods may help improve health information and access to maternity and childcare services. This systematic review was aimed to evaluate the efficacy of m-Health in enhancing the health of children under five in LIMICs. Methodology: A search strategy was carried out in the databases like PubMed, CINAHL, SCOPUS, Science Direct, PsycINFO including some grey literature with a focus on the studies published in English 2013 to 2024 were only included. From a total of 518 studies identified, twenty-two satisfied the criteria for inclusion after a selection process. Results: The results emphasized the impact of m-Health in improving immunization rates, supporting breastfeeding, child growth monitoring, and health-seeking behaviours of the mothers. Text messaging, in particular, has been identified as a cost-effective and widely adopted mobile health approach for behaviour change, adherence to medical recommendations, and promoting healthcare service utilization. Conclusion: The findings underscore the potential of digital health to bridge gaps in healthcare service delivery in resource-limited contexts, addressing critical shortages in human resources and infrastructure.